Human cervical epithelial cells that express HLA-DR associated with viral infection and activated mononuclear cell infiltrate. Issue 4 (April 1991) - Fais, S; Delle Fratte, F; Mancini, F; Cioni, V; Guadagno, M; Vetrano, G; Pallone, F
Abstract : The association between the expression of HLA-DR antigens on cervical epithelium and the local immune state of activation in colposcopically obtained biopsy specimens from patients with histologically documented wart virus infection was investigated. In normal cervical epithelium no HLA-DR staining was detected. No or few IL-2R positive cells were found in the contiguous sections. HLA-DR was expressed by epithelial cells in six out of the 14 samples of wart virus infection. The pattern of fluorescence was focal, but strong and diffuse, to the whole epithelial layer. In the six samples with HLA-DR positive epithelium the numbers of IL-2R positive cells in the lamina propria were strongly increased, ranging between 75 and 90%. HLA-DR expression by cervical epithelium was observed in only two of 12 samples from patients with mixed epithelial non-virus related abnormalities. No increase in the numbers of IL-2R positive cells was observed in this group of patients. Additionally, no significant differences in terms of T lymphocyte infiltrate were found among the three groups. The results indicate that wart virus infection is associated with enhanced HLA-DR epithelial expression and they lend support to the concept that in the human cervix the epithelium actively participates in the local immune response.